The evolution of antifungal therapy: Traditional agents, current challenges and future perspectives - Cássia Milena de Souza; Bárbara Tavares Bezerra; Daniel Agreda Mellon; Haroldo Cesar de Oliveira (Current Research in Microbial Sciences)
Fungal infections kill more than 3 million people every year. This high number reflects the significant challenges that treating these diseases worldwide presents. The current arsenal of antifungal drugs is limited and often accompanied by high toxicity to patients, elevated treatment costs, increased frequency of resistance rates, and the emergence of naturally resistant species. These treatment challenges highlight the urgency of developing new antifungal therapies, which could positively impact millions of lives each year globally. Our review offers an overview of the antifungal drugs currently available for treatment, presents the status of new antifungal drugs under clinical study, and explores ahead to future candidates that aim to help address this important global health issue.